(untitled) (International Seven Journal of Multidisciplinary, 2025)
Idiopathic nephrotic syndrome (INS) in childhood is the most common glomerulopathy in pediatrics and is characterized by nephrotic-range proteinuria, hypoalbuminemia, and edema. Current diagnostic criteria include nephrotic proteinuria defined by a urinary protein-to-creatinine ratio ≥ 2.0 mg/mg (or ≥ 200 mg/mmol) associated with serum albumin < 30 g/L, with laboratory confirmation recommended before initiating treatment (Trautmann et al., 2023). Clinical classification guides management: steroid-sensitive nephrotic syndrome (SSNS) is characterized by complete remission within up to 4 weeks of prednisone, and the definition of frequently relapsing disease (≥ 2 relapses within 6 months or ≥ 3 within 12 months) supports early introduction of steroid-sparing strategies (Trautmann et al., 2023).Recent advances suggest that a subset of INS has a humoral autoimmune basis, with identification of anti-nephrin autoantibodies correlated with disease activity and response to B-cell–depleting therapies (Chan; Boyer, 2025), as well as models in which immune triggers induce anti-podocyte antibodies leading to podocyte injury (Al-Aubodah et al., 2025). In congenital forms (onset < 3 months), the etiology is predominantly genetic, and genetic testing is recommended as first-line evaluation (Boyer et al., 2021). Management includes corticosteroids and, in cases of frequent relapses or steroid dependence, steroid-sparing agents and rituximab in selected cases, with monitoring for hypogammaglobulinemia (Trautmann et al., 2023; Chan; Boyer, 2025). Additionally, evidence-based nutritional management is recommended, avoiding high-protein diets and adjusting sodium restriction according to the clinical phase (Lella et al., 2023; Trautmann et al., 2023). Biomarkers and genotyping support the transition toward precision medicine (Chan; Boyer, 2025; Vincenti; Angeletti; Ghiggeri, 2023).